Better together: Implementation of a patient safety solution committee at an academic cancer center. Issue 28 (1st October 2022) - Bhardwaj, Aarti Sonia; Parra, Jessica; Hussa, Marissa; Mato, John; Tsembelis, Brooke; Jain, Priya; Smith, Cardinale B.
Abstract : 325 Background: The Mount Sinai Health System oncology service line initiated a patient safety solution (PSS) committee to comprehensively review reported safety events in order to provide safe and high-quality care. This multi- and interdisciplinary committee creates a safe space to report events that caused harm, near misses and empowers all staff to be part of a just culture of safety. Here we describe the process and report on outcomes. Methods: The committee consists of nurses, advanced practice providers, physicians, pharmacists, social workers, IT analysts, and administrative staff, representing the oncology service line across inpatient and outpatient. Any staff member can enter incident reports that they believe warrant review into a software application. Our quality team reviews all events and then selects cases in which harm or near-harm was involved, for in-depth investigation to be presented at bi-weekly PSS meetings where cases are discussed, root causes are evaluated, and solutions are proposed. For each case, the committee votes on standard of care using the Continuous Quality Improvement (CQI) Classifications tool. Often, smaller workgroups are formed to carry out quality improvement (QI) projects and corrective action plans (CAPs). All case data, including patient demographics, case summaries, outcomes, and ongoing plans are tracked using a custom REDCap survey. A question about the role of bias was added in December 2020 (yes/no/not enough information). Results: From January 2021 until March 2022, a total of 115 events were reviewed with an average of 23 events reviewed each quarter. Sociodemographic information on patients reviewed is in table. 41% of cases involved the inpatient setting. Issues with medication comprised 47% of cases, followed by patient identification (11%) and lack of escalation (10%). The most common CAPs involved education and counselling (47%), development of new policies (22%) and escalation to leadership (8%). In total, we have developed 29 new workflows, policies, and guidelines. Bias was felt to be involved 25% of the time, no bias 5% and not enough information 43% of the time. Conclusions: This process illustrates the importance of a multi- and interdisciplinary and transparent approach to clinical case and peer review to ensure the highest level of care. The outcomes of this committee have led us to optimize current policies, create new policies and procedures, new rounding structures and place a renewed focus on bias and discrimination.Demographics of reviewed cases. Cases Reviewed (n = 115) Race/Ethnicity N (%) White 40 (35) Black 28 (25) Hispanic 25 (22) Asian 13 (11) Sex Female 58 (51) Male 57 (49) Insurance Medicare 45 (39) Commercial 40 (35) Medicaid 28 (25)